Fairy tales and allegory of Malay(si)an Chinese literature in the early stage of the cold war (1946-1965) - Chiang, Lee Kwun (2021)
Shortly after the end of World War II, the Cold War kicked off. During this time the capitalist and socialist countries headed by the United States and the Soviet Union respectively formed opposing camps. In order to curb China's political interference in the Southeast Asian countries, the United States embarked on a comprehensive policy of containment against China. As a result of these policies even the Chinese diaspora in Malaya could not escape the influence of the Cold War rivalry. This ideological struggle had greatly impacted the Malayan Chinese literature in Malaya during this time. There were many south migrant writers who were active in the Malayan Chinese literary world, writing fairy tales and allegory. The rise and influence of the May Fourth New Literature Movement brought the concept of “People” to the forefront of literature. Many realized that the transformation of people should begin with children. Hence, if the beliefs of May Fourth New Literature Movement had influenced the Malayan Chinese literature, its children’s literature should be taken seriously. Paradoxically, there are only very sparse examples of children’s literature from the 1940s and 1950s to be found in the history of Malayan Chinese literature. This article encapsulates the local translation and creation of fairy tales and allegory by the different factions of literati from China who were active in the Malayan Chinese literary scene into the atmosphere of the two major political battlefields, domestic and international. This article will apply the theories of Walter Benjamin, Terry Eagleton as well as Fredic Jameson, to observe and discuss the following three aspects: Firstly, in what form did the postwar Mahua Children’s Literature mainly appear? What was the definition of children's literature at the time? Secondly, what was the relationship between the Mahua Children’s literature and Mainland Chinese Children’s literature? What was its dominant idea? What role did these migrant Chinese writers had played in this regard? What works had they written and what were the subjects? Thirdly, under the influence of the rivalry Kuomintang and Communist Party of China/leftist and rightist protagonists in Malaya and the Cold War atmosphere, how did the children’s literature in the early days of the Cold War reflect the atmosphere of the above-mentioned era? Through the analysis, it is found that the Mahua Children's Literature in early Cold War period mainly appeared in the form of “history – present – subsequent-history”. It rewrites the novel form of “Shaonian Zhongguo Shuo” by Liang Qichao in modern China, and continued and innovates the fairy tales form that was highly praised by Lu Xun in the May Fourth period. However, these Southern literati from different factions possesed different attitudes towards history, thus various forms and structures have finally evolved. At the time, the definition of children’s literature was "literature that is child-oriented, able to catch the interest of adults, and has the functions of broadening horizons, deepening understanding and tempering children’s mental outlook". This was the form of children’s literature created by southern literati at that time after discovering the problems of Mahua children, with intention to guide them in dealing with the cultural thinking of the Cold War, the Chinese civil war and the colonial situation in Malaya during that time. This literature form reflects the care of the Southern literati towards Mahua Children in that era. In summary, under the influence of the rivalry Kuomintang and the Communist Party of China/left and right camps and the atmosphere of the Cold War, the Mahua Children’s Literature in early Cold War period had reflected the contemporary atmosphere of that era through historical concepts.